PERAN KEPEMIMPINAN APARATUR DALAM MEWUJUDKAN SUMBER DAYA MANUSIA YANG PROFESIONAL PADA BADAN ADMINISTRASI DAN DIKLAT PEGAWAI PROVINSI RIAU - - Asrizal (Pusbindiklat - LIPI, 2010)
In order to implement the function of government, it is needed civil servants who have certain characteristics namely professional, aware and responsive. It is the fact that the function of government is less implemented. In this case, the role of leaders is really required to deal with these matters. The aims of this research are to explain the role of apparatus’ leadership in developing professional state apparatus, to identify the dominant factor, and to formulate a policy which is needed to develop professional civil servants. This study uses a qualitative method.Finding of this research shows that the role of new leader as a planner, teacher, and servant is less optimal. The main factor to realize such role is enhancing professionalism by developing competency of formal education and formulating career pattern development as well as enhancing discipline of civil servants.